Mouse B cells engineered to express an anti-HPV antibody elicit anti-tumor T cell responses - Guberman Bracha, Michal; Biber, Guy; Zelikson, Natalie; Shavit, Sharon; Avraham, Roy; Vagima, Yaron; Bublik, Débora Rosa; Katz, Yael; Barzel, Adi; Klapper, Leah Natasha; Hess, Shmuel; Nahmad, Alessio David (Frontiers in Immunology, 2025)
Transplantation of engineered B cells has demonstrated efficacy in HIV disease models. B cell engineering may also be utilized for the treatment of cancer. Recent studies have highlighted that B cell activity is associated with favorable clinical outcomes in oncology. In mice, polyclonal B cells have been shown to elicit anti-cancer responses. As a potential novel cell therapy, we demonstrate that engineering B cells to target a tumor-associated antigen enhances polyclonal anti-tumor responses. We observe that engineered B cells expressing an anti-HPV B cell receptor internalize the antigen, enabling subsequent activation of oncoantigen-specific T cells. Secreted antibodies from engineered B cells form immune complexes, which are taken up by antigen-presenting cells to further promote T cell activation. Engineered B cells hold promise as novel, multi-modal cell therapies and open new avenues in solid tumor targeting.